The scope of application of the principle of open access to the implementation of tasks financed from public funds (Discourse of Law and Administration, 2022)
The subject of the research concerns the doctrinal significance of the scope of application of the principle of open access to the implementation of tasks financed from public funds. This principle is clearly defined in the Polish Public Finance Act. It expressly provides that all entities have the right to apply for the performance of tasks financed from public funds. Analyzes showed that the scope of application of the principle of open access covers the circumstances in which tasks are financed directly, but also indirectly by public finance sector entities - but for the purpose of performing public goals. This means that this principle also obliges in Poland private entities if they have public funds from which they finance public tasks.
Keywords: principles of managing public funds; public tasks; public funds; financing; entities of the public finance sector